2020
DOI: 10.5152/ejbh.2020.5041
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Comparison of Superflab and Specially Prepared Bolus Materials Used in Radiotherapy Practice

Abstract: European Journal of Breast Health (Eur J Breast Health) is an international, scientific, open access periodical published by independent, unbiased, and double-blinded peer-review principles. It is the official publication of the Turkish Federation of Breast Diseases Societies, and Senologic International Society is the official supporter of the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…We found that the customized helmet bolus was more effective than previous studies using conventional flat bolus and 3D-printed bolus. 26 28 Notably, there was a deviation in dose distribution, indicating a 64%-111.2% difference. The thickness of the scalp blouse may vary depending on the location, which could be a cause for concern as it covers the scalp with a thermoplastic mask.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the customized helmet bolus was more effective than previous studies using conventional flat bolus and 3D-printed bolus. 26 28 Notably, there was a deviation in dose distribution, indicating a 64%-111.2% difference. The thickness of the scalp blouse may vary depending on the location, which could be a cause for concern as it covers the scalp with a thermoplastic mask.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission penumbra arises as a result of the beam coming from the edges of blocks or collimators. It can be reduced by ensuring that the geometry of the focalized blocks accommodate for beam divergence [31].…”
Section: Penumbramentioning
confidence: 99%
“…Despite the availability of commercial bolus, there are still some problems with bolus during radiotherapy. Most commercial boluses are in a flaky structure that does not form adequate contact with the irregular surface of patients’ skin, such as the ear, nose, and scalp, resulting in air gaps between the bolus and the irregular skin[ 5 ]. The resulting air gap is very harmful to obtaining the expected distribution of radiation dose at planning target volume (PTV) for achieving a desired therapeutic outcome[ 6 ].…”
Section: Introductionmentioning
confidence: 99%